ECONOMIC SECURITY OF THE CITY AND BUSINESS SUBJECTS: INTERCONNECTION AND INTERDEPENDENCE - RUDNICHENKO, Yevhenii; HAVLOVSKA, Nataliia; ALEKSIENKO, Oleg; KARABAEV, Vladislav (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article examines the essence of the concept of "system" and "system of economic security of the enterprise", presents the components of the system of economic security of the enterprise highlighted in scientific publications. The relationship between the economic security of the city and the economic security of enterprises is presented. Given the author’s definition of a system, in particular, a system should be understood as a set of elements that form a single whole and are characterized by interconnections between elements, have an input and an output (at least one) to ensure communication with the external environment. According to the table, the concept of system is characterized by the following parameters: set of elements; interconnection of elements into a single whole; presence of relationships between elements. In addition, the system can be characterized from the point of view of regulation theory, in particular: the presence of "inputs" and "outputs"; be characterized by the ability to process information; to be characterized by a law of behavior or features of system functioning; be characterized by governing influences. The system of economic security is a set of interconnected elements aimed at ensuring the security of the enterprise from external threats and challenges. The author’s vision of the economic security system of the enterprise is presented, with the selection of its components, system boundaries and environments (which are related to the system and not related to the system), inputs and outputs. The environment related to the system is the environment that is necessary for understanding the economic security system of the enterprise, the peculiarities of its functioning. The system is characterized by inputs and outputs through which the economic security system interacts with the environment. The article states that the combination of the proposed components of the system (ecological, technical-technological, information, power, intellectual, political-legal, personnel, financial) form an emergent property of the system. A new property (emergent property) appears precisely as a result of combining the components of the enterprise’s economic security system. Management processes take place within the system in order to ensure the properties of the system and achieve the goals of its functioning. The interdependence of the economic security of the city and enterprises has been proven.